The Semiotic Representation Analysis of Wedding Ceremony in West Sumatera Province - Yosi Maeleona Passandaran (Universitas Indraprasta PGRI, 2019)
This study examines the symbolic representations of cultural meanings behind the traditional wedding procession in West Sumatra. This study is a descriptive qualitative study whose data were collected by literature study. The collected data were analyzed using a descriptive approach based on Roland Barthes’s theory of semiotics which includes the discussion on denotative and connotative meaning as well as myth. The results of the analysis were presented in the form of a description of Roland Barthes's semiotic symbols. By examining the marriage procession, there are two interesting topics that can be studied further more. Firstly, the wedding procession itself. Secondly, the variety of materials and objects which are used when performing the traditional wedding procession.